Pronomina Bahasa Melayu dalam Film Nujum Pak Belalang Karya Puteh Ramlee - Tahnia, Rahmi; Dahlan, Saidat; Asnawi, Asnawi (GERAM: Gerakan Aktif Menulis, 2017)
This research entitled "Pronouns Malay Language In Movie Nujum Pak Belalang by Puteh Ramlee". The problem of this research is how is the pronoun of Malay in Nujum Pak Belalang by Puteh Ramlee? The purpose of this research is to know and describe the pronoun of Malay in Nujum Pak Belalang by Puteh Ramlee. The theory used in this research is Alwi, et al (2003), theory Tadjuddin (2013), and theory Ramlan (1990). The approach used in this research is qualitative research, the type of research used in this research included into the research literature and the method used in this research is descriptive method. Data collection techniques of this research are: documentation techniques, references, and techniques of note. Technique of data analysis of this research is classified based on problem which researched in accordance with the object of research. The results indicate that in the movie Nujum Pak Belalang by Puteh Ramlee used the first single person pronouns [hambə], [bəta], and [pati?]. First person plural pronoun [kite]. Single person second pronoun [mikə]. General Pronouns [ni] and [tu].